Environment Impact on Reproductive Health A Translational Approach - Marci, Roberto (Springer International Publishing : Imprint: Springer, 2023)
This open access book focuses on of the impact of endocrine disrupting chemicals (EDCs) on human reproduction. It comprehensively discusses the three most important topics in the field: the basic biology of EDCs; the effects of EDCs on human reproduction and human reproductive systems; and potential interventions and practical advice for dealing with the problems caused by EDCs. Presenting a translational approach to endocrine disrupting chemicals research, spanning both basic biology and clinical applications, the book provides a critical link between laboratory investigations and clinical practice. Written by international experts in the field, it is a valuable reference resource for gynaecologists, obstetricians, endocrinologists and experts in reproductive medicine, and a useful tool for anyone interested in the impact of the environment on human reproduction.